Inhibitory Effect of Litsea cubeba Essential Oil on Aspergillus flavus Growth and Aflatoxin Production - Xiaoxia HUANG; Weibin PENG; Zhenyu LI; Dongrun YANG; Shikun YANG (Shipin gongye ke-ji, 2023)
Litsea cubeba essential oil is a pure natural plant essential oil. In this paper, the inhibitory effect of Litsea cubeba essential oil on the growth, metabolism and toxin production of Aspergillus flavus was investigated. In this study, peanuts were placed in a natural environment to infect bacteria, and the target bacteria were isolated and purified. Morphology and ITS sequence methods were used to classify and identify the strains. The inhibition ability of essential oil on Aspergillus flavus was discussed by the determination of inhibition zone, inhibition rate and minimum inhibitory concentration (MIC). The effects of essential oil on the germination rate, growth curve and aflatoxin B1 production of Aspergillus flavus, as well as the effects of cell membrane permeability and cellular enzyme activity, were tested. The results showed that strain HB2 was isolated and screened from spoilage peanuts and was identified as Aspergillus flavus by the ITS sequence method. The results of aflatoxin determination showed that aflatoxin B1 (AFB1) had a mass concentration of 3.4×103 μg·kg−1 (pure wet bacteria). The bacteriostatic zone significantly increased with increasing essential oil concentration, and the minimum inhibitory concentration (MIC) for Aspergillus flavus was 0.800 μL·mL−1. The germination rate, the length of the dental tube, the growth of Aspergillus flavus, and the concentration of AFB1 showed a significant decreasing trend with increasing concentrations of essential oil in the culture medium. When the concentration of Litsea cubeba essential oil was 0.100 μL·mL−1, the growth of the bacteria was invisible to the naked eye. With the increase in the concentration of essential oil, the conductivity of the culture medium increased, the utilization rate of reducing sugars and the protein content of the bacteria decreased, and the activities of malate dehydrogenase and succinate dehydrogenase in the bacteria decreased. These results indicated that Litsea cubeba essential oil caused irreversible damage to Aspergillus flavus. It is speculated that Litsea cubeba essential oil damaging the cell wall and cell membrane, affecting cell growth and metabolism and ultimately leading to cell death. Therefore, Litsea cubeba essential oil has a good inhibitory effect on Aspergillus flavus and can be widely used in grain storage and food antimolding.